2021
DOI: 10.1155/2021/5495219
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Drug-Coated Balloon in Coronary Patients with and without Diabetes Mellitus: A Multicenter, Propensity Score Study

Abstract: Background. Relative to nondiabetic patients, percutaneous coronary intervention (PCI) in patients with diabetes mellitus (DM) is associated with inferior clinical outcomes. We aimed to evaluate the outcomes of drug-coated balloon (DCB) in diabetic versus nondiabetic patients. Methods and Results. In this observational, prospective, multicenter study, we compared the outcomes of patients with and without DM after undergoing PCI with DCBs. Target lesion failure (TLF) was analyzed as primary endpoint. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Since the first performance of percutaneous coronary angioplasty in 1977 ( Grüntzig, 1978 ), the direct intervention of interventional therapy has been widely used in improving the living quality of patients. The vascular interventional technique (VIT) is an important branch of interventional therapy ( Cao et al, 2021 ; Pan et al, 2021 ), which is commonly used in the treatment of cardiovascular diseases (e.g., atherosclerosis). Although the clinical application is quite mature, adverse clinical events ( Daemen et al, 2007 ; Faxon, 2012 ; Qiu et al, 2021 ) including late thrombosis and intimal hyperplasia are still long-term side effects of the VIT.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first performance of percutaneous coronary angioplasty in 1977 ( Grüntzig, 1978 ), the direct intervention of interventional therapy has been widely used in improving the living quality of patients. The vascular interventional technique (VIT) is an important branch of interventional therapy ( Cao et al, 2021 ; Pan et al, 2021 ), which is commonly used in the treatment of cardiovascular diseases (e.g., atherosclerosis). Although the clinical application is quite mature, adverse clinical events ( Daemen et al, 2007 ; Faxon, 2012 ; Qiu et al, 2021 ) including late thrombosis and intimal hyperplasia are still long-term side effects of the VIT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that patients with DM have more diffuse and complex CAD than non-diabetic patients, which is also consistent with the current study that patients with diabetes had a smaller diameter of the coronary artery, longer lesions and more serious lesions. [17][18][19] These researches demonstrated that CAD in the presence of DM has unique characteristics. The high risk of MACE in patients with diabetes may be secondary to the complex pathophysiological mechanisms, including endothelial dysfunction, chronic inflammation, and activation of platelet.…”
mentioning
confidence: 99%
“…16 One of the beneficial feature of DCB is the local delivery of paclitaxel to coronary artery without leaving metal sten. 17 As a result, DCB decreased the incidence and de novo lesion, especially in small vessel disease. 17,18 However adverse events risk in patients with diabetes treated with DCB had not been fully assessed.…”
mentioning
confidence: 99%
See 2 more Smart Citations